GERAY DASIF: Gerakan Ayah Dukung Asi Eksklusif di Wilayah Kerja Puskesmas Peusangan Siblah Krueng - Fitriani, Aida; Wahyuni, Yenni Fitriani; Fitraniar, Iin; Friscila, Ika (Nusantara Mengabdi Kepada Negeri, 2024)
Many fathers are concerned about the low level of breastfeeding, but fathers do not show any action to provide proper support to their wives. The problem of exclusive breastfeeding also occurs in the Peusangan Siblah Krueng Health Center Work Area with babies aged 0-6 months who do not receive exclusive breastfeeding. This cannot be allowed to continue because exclusive breastfeeding is the main source of nutrition for growth and development. Activity Objectives: Creating GERAY DASIF: Fathers' Movement to Support Exclusive Breastfeeding in the Dewantara Health Center Work Area and increasing the active involvement of fathers in improving maternal and infant health. Community Service Methods: Identification of exclusive breastfeeding, identification of supporting factors for breastfeeding mothers in North Aceh, consultation and formation of fathers' groups, group management, monitoring and evaluation, activity reports, scientific publications, socialization. The result of the service is the formation of a group of fathers supporting exclusive breastfeeding so that fathers are aware of their role which is not only to earn a living but also "but fathers/husbands also play a big role in providing support for the family, especially for partners (wives), one of which is supporting or helping mothers (wives) in terms of providing breast milk so that mothers feel able to breastfeed their babies and get attention from their husbands.